Evaluation of resistance to neck rot by Sclerotium rolfsii Sacc. in chickpea genotypes - Guerrero-Aguilar, Brenda Zulema; Martínez-Martínez, Alina A.; González-Chavira, Mario M.; Jorge A.; Ortega-Murrieta, Pedro Francisco; Fierros-Leyva, Gustavo (Revista Mexicana de Ciencias Agrícolas, 2024)
They were collected from plants with symptoms of yellowing and wilting in commercial chickpea fields in five municipalities in southern Guanajuato, Mexico. From these, the pathogens present in the stem and root were isolated and identified. Of the isolates obtained, those with morphological characteristics of Sclerotium rolfsii had their identity confirmed by sequencing the ITS fragments obtained with the oligonucleotides: NsiF and Nlb4R; the sequences obtained were compared with the NCBI database. Of the two isolates identified as S. rolfsii by both methodologies, the most virulent was identified, which was used to inoculate 181 chickpea genotypes of the kabuli and desi types. The results indicate that, according to the mortality percentage, the genotypes of the desi type ICC3287, ICC 4874, ICC1882, ICC 10259 and WR-315, and kabuli type CUGA 08-3160 presented moderate resistance to the pathogen. Of these resistant genotypes, ICC 10259 stands out, which has genetic resistance to four races of Fusarium oxysporum f. sp. ciceris and M. phaseolina.